2022
DOI: 10.1039/d1cy02102h
|View full text |Cite
|
Sign up to set email alerts
|

Direct SVUV-PIMS identification of unstable oxygenated intermediates in ethanol to butadiene reaction

Abstract: Unstable oxygenated intermediates widely exist in biomass catalytic reaction but difficult to experimentally observed. Synchrotron-based vacuum ultraviolet photoionization mass spectrometry (SVUV-PIMS) was employed for identification of the unstable oxygenate intermediates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is argued that these species are formed either via direct surface reaction between AL and ethanol, 11,90 or by Meerwein-Ponndorf-Verley (MPV) reduction of CAD, which is obtained from AL by aldol addition and condensation. 13,55,91,92 Recently, Yang et al 28 successfully identified the aldol addition product 3-hydroxybutanal (i. e., acetaldol), the intermediate of CAD, but not under commonly used reaction conditions. We never detected acetaldol and never found CAD in the product mixture in concentration that could be considered as strong enough evidence for the role of CAD or CAD-like surface species as an intermediate of the ETB reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is argued that these species are formed either via direct surface reaction between AL and ethanol, 11,90 or by Meerwein-Ponndorf-Verley (MPV) reduction of CAD, which is obtained from AL by aldol addition and condensation. 13,55,91,92 Recently, Yang et al 28 successfully identified the aldol addition product 3-hydroxybutanal (i. e., acetaldol), the intermediate of CAD, but not under commonly used reaction conditions. We never detected acetaldol and never found CAD in the product mixture in concentration that could be considered as strong enough evidence for the role of CAD or CAD-like surface species as an intermediate of the ETB reaction.…”
Section: Discussionmentioning
confidence: 99%
“…1 The potential of heterogeneous catalytic ETB process has even been demonstrated at industrial level. 2 The most commonly used supports/catalysts for the reaction are mixed oxides, such as MgO-SiO 2 3,4,[13][14][15][16][17][18][19][20][21][22]5,[23][24][25][26][27][28][29][6][7][8][9][10][11][12] or ZrO 2 -SiO 2 [30][31][32][33][34] , and their derivatives, obtained through modification by metals, such as, Ag 4,27,31,35,36 , Cu 16,27,33 , and Au 10 , or by metal oxides ZrO 2 9,36,37 , ZnO 9,16,19,23,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation